Rapid electrochemical reduction of a typical chlorinated organophosphorus flame retardant on copper foam: degradation kinetics and mechanisms. (February 2021) - Yang, Liansheng; Huang, Chuyi; Yin, Ze; Meng, Jiaqi; Guo, Min; Feng, Li; Liu, Yongze; Zhang, Liqiu; Du, Ziwen
Abstract: With the widespread use, chlorinated organophosphorus flame retardants (Cl-OPFRs) as a new emerging contaminant have been widely detected in water environments over the last few years. In this study, the degradation of a typical Cl-OPFR, TCEP (tris (2-chloroethyl) phosphate), by electrochemical reduction was investigated. It was found that copper (Cu) foam as the cathode showed more rapid and effective degradation for TCEP, compared to other cathodes. When TCEP was at the low concentrations (0.1 and 1 mg L −1 ), its degradation by Cu foam could reach above 95% within 20 min, and the maximum rate constant was 0.127 min–1. TCEP reduction was little influenced by the co-existing humic substance and anions, except Cl − . Compared with the reported oxidation methods, electrochemical reduction showed fast and stable degradation for TCEP. For other types of Cl-OPFRs, electrochemical reduction displayed a fast and effective removal for tris (1, 3-dichloro-2-propyl) phosphate but lower removal for tris (2-cholroisopropyl) phosphate who possessed methyl units in the branched chains, influencing its reducibility. Based on the product analysis and Fukui function calculation, the bonds of TCEP molecule were found to be gradually broken, and the three oxygen-ethyl-chlorine arms were cleaved one by one. The products including C6 H13 Cl2 O4 P (MW = 249.99278 Da), C4 H9 Cl2 O4 P (MW = 221.96105 Da) and C4 H10 ClO4 P (MW = 188.0002 Da) were detected at 60 min reaction, and those intermediates showed much lower toxicities than TCEP according to the previous report. The findings may provide a promising treatment for Cl-OPFRs removal from aqueous environments and help understand their reductive fate. Graphical abstract: Image 1 Highlights: Electrochemical reduction showed rapid and effective degradation for TCEP. The degradation effectiveness of TCEP by Cu foam cathode was higher than other materials. TCEP reduction was slightly influenced by co-existing HA and inorganic ion expect Cl − . C–Cl, C–C and C–O bonds of TCEP molecules were cleaved during reduction process.